Inferring shallow surfaces on sub-neptune exoplanets with JWST - Tsai, S-M; Innes, H; Lichtenberg, T; Taylor, J; Malik, M; Chubb, K; Pierrehumbert, R (IOP Publishing, 2021)
Planets smaller than Neptune and larger than Earth make up the majority of the discovered exoplanets. Those with H2-rich atmospheres are prime targets for atmospheric characterization. The transition between the two main classes, super-Earths and sub-Neptunes, is not clearly understood as the rocky surface is likely not accessible to observations. Tracking several trace gases (specifically the loss of ammonia (NH3) and hydrogen cyanide (HCN)) has been proposed as a proxy for the presence of a shallow surface. In this work, we revisit the proposed mechanism of nitrogen conversion in detail and find its timescale on the order of a million years. NH3 exhibits dual paths converting to N2 or HCN, depending on the UV radiation of the star and the stage of the system. In addition, methanol (CH3OH) is identified as a robust and complementary proxy for a shallow surface. We follow the fiducial example of K2-18b with a 2D photochemical model on an equatorial plane. We find a fairly uniform composition distribution below 0.1 mbar controlled by the dayside, as a result of slow chemical evolution. NH3 and CH3OH are concluded to be the most unambiguous proxies to infer surfaces on sub-Neptunes in the era of the James Webb Space Telescope.